Building trust: A multiple case study of teenagers’ and foster parents’ relationships - Dalgaard, Nina Thorup; Ramsbøl, Anne Toft; Væver, Mette Skovgaard; Pontoppidan, Maiken (Adoption & fostering, 2025)
This multiple case study explores the experiences of five teenagers in foster care and their foster parents in Denmark, focusing on their perceptions of foster care and relationship dynamics. Through qualitative interviews, three key themes emerged: (1) The impact of early traumatic experiences on current wellbeing; (2) Foster parent–teenager relationships; (3) Relationships with biological families, where teenagers maintain differing levels of contact and express mixed feelings. Drawing on Fonagy and Allison’s (2014) concept of epistemic trust, as applied to foster care by Sprecher (2023), the study highlights the complexities of foster parent–teenager relationships, illustrating both challenges and the potential for trust and connection. While some teenagers experienced strong, supportive relationships with their foster parents, others faced difficulties in developing epistemic trust and fully integrating into their foster families. Discrepancies between foster parent and teenager perspectives suggest that foster parents are generally less optimistic than the teenagers themselves regarding their foster teenagers’ future outlook. These findings highlight the importance of relationship-based practice in foster care, where understanding each teenager's individual relational history and trust needs may be crucial for supporting positive development. Plain language summary This multiple case study examines the experiences of five teenagers in foster care and their foster parents in Denmark, focusing on their perceptions of foster care and the dynamics of their relationships. Through qualitative interviews, three key themes emerged. The first theme explores early traumatic experiences and life in foster care, where both foster teens and foster parents reflect on how the teenagers’ past experiences impact their current wellbeing and life in foster care. Foster parents generally expressed more concerns about the teenagers’ future than the teenagers themselves. The second theme focuses on foster parent–teenager relationships, in which teenagers and their foster parents report positive connections, although there are differences in how close they perceive their relationship with each other to be. The third theme examines relationships with biological parents and siblings, where the teenagers maintain varying degrees of contact with their biological families and express mixed feelings about these relationships. These findings highlight the importance of relationship-based practice in foster care, where understanding each teenager’s individual relational history and trust needs may be crucial for supporting positive development.